2000
DOI: 10.1300/j069v19n04_02
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cigarette Smoking and Drug Abuse in the United States

Abstract: Cigarette smoking has been identified as an independent risk factor for many human diseases. However, the association between cigarette smoking and illegal drug use has not been thoroughly investigated. We have analyzed the 1994 National Household Survey on Drug Abuse to clarify whether cigarette smoking has any effect on the initiation of illegal drug use. Data from 17,809 respondents completing the 1994 "new" (1994-B) questionnaire were analyzed. Logistic regression analyses were performed with the use of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 16 publications
12
116
1
9
Order By: Relevance
“…Although such co-dependence may reflect genetic or social factors, several clinical studies have suggested that adolescent smoking may increase the subsequent use of other addictive substances (Grucza and Bierut, 2006;Torabi et al, 1993;Lai et al, 2000;Biederman, 2005;Palmer et al, 2009). Our findings provide evidence that nicotine administration during adolescence causes long-lasting behavioral and neurochemical adaptations, and elucidate novel pathways altered by nicotine that may increase vulnerability to high-risk behaviors.…”
Section: Discussionmentioning
confidence: 56%
“…Although such co-dependence may reflect genetic or social factors, several clinical studies have suggested that adolescent smoking may increase the subsequent use of other addictive substances (Grucza and Bierut, 2006;Torabi et al, 1993;Lai et al, 2000;Biederman, 2005;Palmer et al, 2009). Our findings provide evidence that nicotine administration during adolescence causes long-lasting behavioral and neurochemical adaptations, and elucidate novel pathways altered by nicotine that may increase vulnerability to high-risk behaviors.…”
Section: Discussionmentioning
confidence: 56%
“…Conversely, tobacco use increases the likelihood of experimentation with illicit drug use (Lai, et al, 2000). Also, tobacco and other substance use are highly predictive of youth engagement in multiple risk behaviors including bicycling without a helmet, violence and weapon carrying, not using a seatbelt, and suicidal ideation (DuRant, et al, 1999).…”
Section: Rationale For Mhbc Researchmentioning
confidence: 99%
“…No entanto, não foi objetivo deste estudo avaliar a presença de comorbidade, não sendo avaliado o tempo de abstinência do crack ou da cocaína em cada ato infracional, o que seria fundamental para excluir a possibilidade de um transtorno induzido pelo uso da substância [10][11][12][13][14][15][16][17][18] .…”
Section: Tabela 3 -Antecedentes Criminais Dos Usuários De Crack Interunclassified
“…Nesse sentido, Lai et al 13 demonstraram que pessoas tabagistas são mais propensas a usar cocaína e crack, e Parry et al 3 identificaram ser prevalente o uso primário e secundário de outras substâncias psicoativas, havendo um destaque para o álcool e a maconha. Deve-se ressaltar que, no estudo desses autores 3 , não foi avaliado o uso de tabaco.…”
Section: Introductionunclassified